Hydrodynamic analysis for underwater vehicle recovery through dock integrated supporting vessel based on experimental investigation, part I: Wave sensitivity analysis - Guo Wang; Zerun Wang; Junbo Ge; Yunxiang You; Aichun Feng (Ocean Engineering, 2026)

Numerical investigation of straight-line navigation motion response of the under-water vehicle under irregular waves - Guo Wang; Junbo Ge; JingJing Zhang; Yunxiang You; Panpan Han (Ocean Engineering, 2026)

Carbon-chain length dictates per- and polyfluorinated substance potency as inhibitors of human and rat 11β-hydroxysteroid dehydrogenase 1 - Congcong Zhao; Zhiqiang Yu; Mengyun Wang; Yingfen Ying; Yunbing Tang; Huitao Li; Ren-shan Ge; Junbo Liang (Toxicology and Applied Pharmacology, 2026)

Loss of eIF3m aggravates myocardial ischemia/reperfusion injury via enhancing nitrative damage and inhibiting glycolytic reprogramming - Zilun Wei; Yongchao Zhao; Daile Jia; Rifeng Gao; Weidong Xiong; Xiaolei Sun; Xinyu Weng; Bowen Liu; Shuai Song; Wei Luo; Jian Cui; Kai Hu; et al. (Science Bulletin, 2026)

Environmental eustress inhibits CCL2 to overcome doxorubicin-induced cardiotoxicity and alleviate tumor growth - Peiyuan Bai; Chaobao Liu; Ao Liu; Zehao Zhuang; Jinghong Zhang; Lu Tang; Naifu Wan; Runda Wu; Wuwei Rong; Siqin Chen; Jinglei Wan; Yang Yang; et al. (Science Bulletin, 2026)

SIRT6 alleviates ischemic injury via orchestrating the RREB1/Snail and STC1/Smad7 signaling pathways to regulate endothelial-mesenchymal transition - Zhentao Zhang; Zheyan Fang; Shuang Zhao; Mukaddas Abdurahman; Gang Zhao; Runyang Feng; Zhenyang Guo; Xueting Yu; Hangnan Hong; Jilong Geng; Xiansu Nie; Supuya Abuduwahapi; et al. (Science China Life Sciences, 2026)

Multifunctional sericin/alginate hydrogel integrated with cerium oxide nanozyme for accelerating methicillin-resistant Staphylococcus aureus-infected wound healing - Haiyang Liu; Yingjie Shen; Xin Xie; Xudong Mao; Jin Ren; Cunming Peng; Liangliang Wang; Junbo Zhou; Le Zhang; Lulu Zhang; Changchun Peng; Haixia Ge; et al. (Chemical Engineering Journal, 2026)

Ostracod assemblages and their relationship with water depth in surface sediments of Nam Co, Tibetan Plateau - Tao Xu; Yang Zhang; Manping Xie; Junbo Wang; Huaxiu Hu; Dingkuan Ge (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The FLOW Framework: a panvascular-on-a-chip platform to model systemic disease and guide panvascular interventional device suitcordance - Lingsen You; Yuheng Chen; Zeyang Zhang; Yu Wang; Zhongze Gu; Li Shen; Junbo Ge (Science Bulletin, 2026)

Comparison investigation of hydrodynamic responses for SUBOFF travelling on and near free surface - Dahui Ge; Yucai Chen; Guo Wang; Junbo Ge; Yunxiang You; Aichun Feng (Ocean Engineering, 2026)

Numerical investigation for shielding effects of two vessels in side-by-side configurations - Wei Wang; Dahui Ge; Guo Wang; Junbo Ge; Yihan Zhao; Aichun Feng (Ocean Engineering, 2025)

Enhancing panvascular medicine: unveiling the nexus of pan-cardio-oncology and expanding therapeutic frontiers - Yiqing Hu; You Zhou; Neng Dai; Shuai Song; Xin Zhao; Yongchao Zhao; Leilei Cheng; Hao Lu; Junbo Ge (Science Bulletin, 2025)

Image recognition enhances efficient monitoring of the coagulation-settling in drinking water treatment plants - Hongbo Liu; Yang Chen; Xuwei Pan; Junbo Zhang; Jianhong Huang; Eric Lichtfouse; Gang Zhou; Haiyu Ge (Journal of Cleaner Production, 2024)

TRIM25-mediated XRCC1 ubiquitination accelerates atherosclerosis by inducing macrophage M1 polarization and programmed death - Hongxian Wu; Wei Gao; Yuanji Ma; Xin Zhong; Juying Qian; Dong Huang; Junbo Ge (Inflammation Research, 2024)

Corrigendum to “Transplantation of mitochondria encapsulated in hydrogel ameliorates myocardial ischemia-reperfusion injury” [Chem. Eng. J. 460 (2023) 141799] - Ya Huang; Xiaolei Sun; Rifeng Gao; Liwei Zhang; Hang Chen; Yang Lv; Xiang Wei; Yunzeng Zou; Kai Hu; Aijun Sun; Junbo Ge (Chemical Engineering Journal, 2024)

Automatic identification of factor profiles can be achieved by improved machine learning model - Bo Xu; Junbo Huang; Yi Ge; Chun Zhang; Han Xu; Feng Wang; Huan Zhao; Linlin Zhang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Environment, 2024)

Ionic liquid microwave-assisted hydrodistillation extraction of Angelica sinensis essential oil and its own anti-inflammatory and antioxidant activities - Taotao Li; Huanxian Shi; Wenfei Wang; Jia Li; Tiantian Tang; Yujiao Wang; Ding Liu; Kai Yang; Xuan Wang; Jie Wang; Ning Xia; Jinhui Wang; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Robust Positioning Estimation for Underwater Acoustics Targets with Use of Multi-Particle Swarm Optimization - Xiyun Ge; Hongkun Zhou; Junbo Zhao; Xiaowei Li; Xinyu Liu; Jin Li; Chengming Luo (Journal of Marine Science and Engineering, 2024)
With the extensive application of sensor technology in scientific ocean research, ocean resource exploration, underwater engineering construction, and other fields, underwater target positioning technology has become an important support for the ocean field. This paper proposes a robust positioning algorithm that combines the disadvantages of distributed estimation and particle swarm optimization, which can solve the large localization error problem caused by uncertainties in underwater acoustic communication and sampling processes. Considering the presence of ranging anomalies and sampling packet loss in underwater acoustic measurements, a weighted coupling filling method is used to correct the outliers in an underwater acoustic ranging signal. Based on the mapping model from the element array to the underwater acoustic responder, an unconstrained optimization algorithm for one-time localization estimation of underwater acoustic targets was established. Based on the one-time localization estimation results of underwater acoustic targets, an improved multi-particle swarm optimization estimation based on interactive search is proposed, which improves the accuracy of underwater target localization. The numerical results show that the positioning accuracy of the proposed algorithm can be effectively enhanced in cases of distance measurement errors and azimuth measurement errors. Compared with the positioning error before optimization, the positioning error can be reduced after optimization. Additionally, the experiment was carried out in the underwater environment of Hangzhou Qiandao Lake, which verified the positioning performance of the proposed algorithm.

Trajectory tracking control of two-joint underwater manipulator in ocean-wave environment - Dahui Ge; Guo Wang; Junbo Ge; Bing Xiang; Yunxiang You; Aichun Feng (Ocean Engineering, 2024)

Machine learning reveals the effects of drivers on PM2.5 and CO2 based on ensemble source apportionment method - Han Xu; Yi Ge; Chun Zhang; Zhenyu Wang; Bo Xu; Huan Zhao; Junbo Huang; Gen Wang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Research, 2023)

Hypoxia and panvascular diseases: exploring the role of hypoxia-inducible factors in vascular smooth muscle cells under panvascular pathologies - Yiqing Hu; Yongchao Zhao; Peng Li; Hao Lu; Hua Li; Junbo Ge (Science Bulletin, 2023)

Netrin-3 Suppresses Diabetic Neuropathic Pain by Gating the Intra-epidermal Sprouting of Sensory Axons - Weiping Pan; Xueyin Huang; Zikai Yu; Qiongqiong Ding; Liping Xia; Jianfeng Hua; Bokai Gu; Qisong Xiong; Hualin Yu; Junbo Wang; Zhenzhong Xu; Linghui Zeng; et al. (Neuroscience Bulletin, 2023)

Random walk multipath method for Galileo real-time phase multipath mitigation - Mingxian Hu; Yibin Yao; Maorong Ge; Frank Neitzel; Junbo Shi; Peifen Pan; Meihao Yang (GPS Solutions, 2023)

Recent advances in the gut microbiome and microbial metabolites alterations of coronary artery disease - Yuxiang Dai; Zhonghan Sun; Yan Zheng; Junbo Ge (Science Bulletin, 2023)

Transplantation of mitochondria encapsulated in hydrogel ameliorates myocardial ischemia-reperfusion injury - Ya Huang; Xiaolei Sun; Rifeng Gao; Liwei Zhang; Hang Chen; Yang Lv; Xiang Wei; Yunzeng Zou; Kai Hu; Aijun Sun; Junbo Ge (Chemical Engineering Journal, 2023)

Targeted delivery of platelet membrane modified extracellular vesicles into atherosclerotic plaque to regress atherosclerosis - Qiyu Li; Zheyong Huang; Zhiqing Pang; Qiaozi Wang; Jinfeng Gao; Jing Chen; Zhengmin Wang; Haipeng Tan; Su Li; Fei Xu; Jinxiang Chen; Muyin Liu; et al. (Chemical Engineering Journal, 2023)

Mitochondrial gene rearrangements suggest a new genus in the subfamily Cantharinae (Coleoptera) - Yuxia Yang; Ya Kang; Junbo Tong; Xueying Ge; Xingke Yang; Haoyu Liu (Zoologica Scripta, 2023)
The Cephalomalthinus semifumatus species group, referred to as the “semifumatus” group henceforth, is interesting because of its heterogeneous morphology resembling either Cephalomalthinus Pic, 1921 or Rhagonycha Eschscholtz, 1830. To elucidate its phylogenetic status, mitochondrial genomes of four species of the “semifumatus” group, 11 Cephalomalthinus species, and 11 Rhagonycha species were sequenced and examined. All analysed mitogenomes were similar with respect to genome size, nucleotide composition, and AT content. Surprisingly, a rearrangement of the trnW ‐ trnC and trnY genes was detected in the “semifumatus” group, presumably caused by tandem duplication and random loss events. Furthermore, genetic distance analyses showed that the proximity of the “semifumatus” group to Cephalomalthinus and to Rhagonycha was comparable to that between the latter two. Moreover, the produced phylogeny strongly supported the monophyly of the “semifumatus” group, and molecular clock analyses dated its divergence from Cephalomalthinus to 32.52 Ma. Thus, the new genus Amphimorphus gen. nov. is suggested to comprise the “semifumatus” group, in which the observed gene rearrangement was a synapomorphy. Moreover, morphological evidence regarding the unique structure of the aedeagus supported this separation. These results indicate that mitochondrial gene rearrangement provide important phylogenetic implications for revising Cephalomalthinus , a speciose genus that is puzzling in the morphology‐based taxonomy.

Twin peaks of in-hospital mortality among patients with STEMI across five phases of COVID-19 outbreak in China: a nation-wide study - Jianping Li; Nan Zhang; Ziyi Zhou; Xiao Huang; Weiyi Fang; Hongbing Yan; Jiyan Chen; Weimin Wang; Dingcheng Xiang; Xi Su; Bo Yu; Yan Wang; et al. (Science China Life Sciences, 2022)

Rosuvastatin Alleviates Coronary Microembolization-Induced Cardiac Injury by Suppressing Nox2-Induced ROS Overproduction and Myocardial Apoptosis - Yuanyuan Cao; Zhangwei Chen; Jianguo Jia; Ao Chen; Yanhua Gao; Juying Qian; Junbo Ge (Cardiovascular Toxicology, 2022)

Origin and Spread of the ALDH2 Glu504Lys Allele - Xiaokai Zhang; Aijun Sun; Junbo Ge (Phenomics, 2021)
Gene polymorphism of acetaldehyde dehydrogenase 2 (ALDH2), a key enzyme for alcohol metabolism in humans, can affect catalytic activity. The ALDH2 Glu504Lys mutant allele has a high-frequency distribution in East Asian populations and has been demonstrated to be associated with an increased risk of cardiovascular disease, stroke, and tumors. Available evidence suggests that the evolution of the ALDH2 gene has been influenced by multiple factors. Random mutations produce Glu504Lys, and genetic drift alters the frequency of this allele; additionally, environmental factors such as hepatitis B virus infection and high-elevation hypoxia affect its frequency through selective effects, ultimately resulting in a high frequency of this allele in East Asian populations. Here, the origin, selection, and spread of the ALDH2 Glu504Lys allele are discussed, and an outlook for further research is proposed to realize a precision medical strategy based on the genetic and environmental variations in ALDH2.

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

LncRNA NRON alleviates atrial fibrosis via promoting NFATc3 phosphorylation - Yapeng Wang; Peng Xu; Chengxin Zhang; Junbo Feng; Wenhui Gong; Shenglin Ge; Zhixiang Guo (Molecular and Cellular Biochemistry, 2019)

Mitochondrial aldehyde dehydrogenase 2 deficiency aggravates energy metabolism disturbance and diastolic dysfunction in diabetic mice - Cong Wang; Fan Fan; Quan Cao; Cheng Shen; Hong Zhu; Peng Wang; Xiaona Zhao; Xiaolei Sun; Zhen Dong; Xin Ma; Xiangwei liu; Shasha Han; et al. (Journal of Molecular Medicine, 2016)

Role of methylenetetrahydrofolate reductase 677C→T polymorphism in the development of myocardial infarction: evidence from an original study and updated meta-analysis - Wenbin Zhang; Min Wang; Pei Zhang; Zhimin Xue; Guosheng Fu; Junbo Ge; Yi Luan (Genes & Genomics, 2016)

Hydrogen sulfide suppresses transforming growth factor-β1-induced differentiation of human cardiac fibroblasts into myofibroblasts - YouEn Zhang; JiaNing Wang; Hua Li; LiangJun Yuan; Lei Wang; Bing Wu; JunBo Ge (Science China Life Sciences, 2015)

miR-210 over-expression enhances mesenchymal stem cell survival in an oxidative stress environment through antioxidation and c-Met pathway activation - JianFeng Xu; ZheYong Huang; Li Lin; MingQiang Fu; YanHua Gao; YunLi Shen; YunZeng Zou; AiJun Sun; JuYing Qian; JunBo Ge (Science China Life Sciences, 2014)

Isolation, Culture, and Identification of Amniotic Fluid-Derived Mesenchymal Stem Cells - Xuetao Fei; Shan Jiang; Song Zhang; Yigang Li; Junbo Ge; Ben He; Steven Goldstein; George Ruiz (Cell Biochemistry and Biophysics, 2013)

The Effect of c-fos on Acute Myocardial Infarction and the Significance of Metoprolol Intervention in a Rat Model - Song Zhang; Meiqi Zhang; Steven Goldstein; Yigang Li; Junbo Ge; Ben He; George Ruiz (Cell Biochemistry and Biophysics, 2013)

High density lipoprotein cholesterol promotes the proliferation of bone-derived mesenchymal stem cells via binding scavenger receptor-B type I and activation of PI3K/Akt, MAPK/ERK1/2 pathways - Jianfeng Xu; Juying Qian; Xinxing Xie; Li Lin; Jianying Ma; Zheyong Huang; Mingqiang Fu; Yunzeng Zou; Junbo Ge (Molecular and Cellular Biochemistry, 2012)

Isolation of yellow catfish β-actin promoter and generation of transgenic yellow catfish expressing enhanced yellow fluorescent protein - Jiachun Ge; Zhangji Dong; Jingyun Li; Zhiqiang Xu; Wei Song; Jie Bao; Dong Liang; Junbo Li; Kui Li; Wenshuang Jia; Muzi Zhao; Yongxiang Cai; et al. (Transgenic Research, 2012)

The role of SDF-1α/Rac pathway in the regulation of endothelial progenitor cell polarity; homing and expression of Rac1, Rac2 during endothelial repair - Li Shen; Yongxing Gao; Juying Qian; Yizhe Wu; Mingming Zhou; Aijun Sun; Yunzeng Zou; Junbo Ge (Molecular and Cellular Biochemistry, 2012)

Heat shock transcription factor 1 inhibits H2O2-induced cardiomyocyte death through suppression of high-mobility group box 1 - Ying Yu; Ming Liu; Lei Zhang; Quan Cao; Peipei Zhang; Hong Jiang; Yunzeng Zou; Junbo Ge (Molecular and Cellular Biochemistry, 2012)

Heat shock transcription factor-1 inhibits H2O2-induced apoptosis via down-regulation of reactive oxygen species in cardiac myocytes - Lei Zhang; Hong Jiang; Xiaoqing Gao; Yunzeng Zou; Ming Liu; Yanyan Liang; Ying Yu; Weidong Zhu; Haozhu Chen; Junbo Ge (Molecular and Cellular Biochemistry, 2011)

The relationship between human cytomegalovirus infection and atherosclerosis development - Ruizhen Chen; Sidong Xiong; Yingzhen Yang; Weiguo Fu; Yuqi Wang; Junbo Ge (Molecular and Cellular Biochemistry, 2003)